“The factors that influence the effectiveness of the promotional activities at Binaraya PKINK Sdn Bhd“ / Khairiyatul Mu’minah Mis - Mis, Khairiyatul Mu’minah (Faculty of Business and Management, 2008)
Fluctuation of market nowadays gives impacts to the people. The demand of house projects decrease due to the increase of related cost of the projects. Due to that, the researcher conducted this study to identify the factors that influencing the effectiveness of promotional activities at BINARAYA Pkink Sdn. Bhd. The factors and also the independent variables are advertising, online marketing and personal selling. Dependent variable is the effectiveness of promotional activities. The objective of this study is to examine the impact of each independent variable to its dependent variable as well as to conclude the relationships exist. The researcher used exploratory research design as it attempts to determine the effectiveness of promotional activities. At the same time it also determines the degree to which variables are associated. In collecting the data, the researcher obtains from primary from questionnaires, interviews and observation while secondary data collected from journals, articles, books, reports and internet. Simple random sampling was used for this study as it allows obtaining a sample of convenient elements as well as accessible, easy to measure and cooperative. Due to that, 100 respondents selected randomly to answer questionnaires which the researcher focused on BINARAYA's staffs and clients. Then the researcher analyzed the data from questionnaires using Statistical Package for Social Science 14.0 Students Version. Data was interpreted and test using frequency distribution analysis. Correlation analysis, correlation coefficient and simple regression used to test hypotheses. The results show that all three independent variables have positive relationships with dependent variables. In terms of regression analysis, the most effective promotional activity is advertising and the most ineffective promotional activity is online marketing. Recommendations outline by the researcher are active online marketing program widely. The BINARAYA can stress on the website and update the latest news about current projects. Then, the BINARAYA can pursue with creative advertising seems it's attract more than other promotional activities